MOTIVASI INDONESIA MENERAPKAN KEBIJAKAN PENGAMPUNAN PAJAK TAHUN 2016-2017 - Putri, Mirda Awalia; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to explain the interest of Indonesia implement tax amnesty in 2016-2017. Currently, taxes are the dominant source of state budget. Almost 70% of state revenue comes from the tax sector. However, the tax collection system in Indonesia has not been able to run well. This has resulted in a lack of tax revenues that can be used for state development. In order to increase tax revenue, Indonesia implements tax amnesty policy. The policy is valid since its enactment on July 2016 that is with the issuance of Law no. 11 of 2016.Data of this research was obtained from books, journals, articles, official documents and websites that support the hyphothesis. The author used Neo-merkantilism approach by Robert Gilpin. The theories used in this research concist of International Relations and Economic Growth by Harrod-Domar, and National Interest by Hans J. Morgenthau.The result of this research shows that there is an economic politic interest of in the implementation of tax amnesty policy in 2016-2017. With the adoption of this policy, Indonesia can improve its taxation data base and reform it, which is a taxation politic to participate in Automatic Exchange of Information (AEoI) cooperation in the section of taxation. A good taxation database will also increase tax revenues.Keywords: Tax, Tax Amnesty, National Interest